The Analysis of Time-Driven Activity-Based Costing to Increase Customer Profitability: (A Case Study of Distributor Company) - Feki Wahyu Colimah; Lindawati Gani (Universitas Pendidikan Ganesha, 2024)
This research aims to implement and analyze the concept of time-driven activity-based costing (TDABC) to allocate the cost of serving customers to their accounts, analyze customer profitability, and formulate strategic decisions to increase customer profitability. The study employs a case study strategy with a mixed methods research approach, utilizing various research tools to obtain detailed data. The collected data is analyzed using descriptive analysis with explanation-building techniques. The results reveal that the ten largest customers were profitable for Company A in 2021; however, the most significant profit was not generated by customers who contributed the greatest revenue, and vice versa. The customer profitability analysis indicates that two customers require the highest service priority and care, seven customers should be managed with periodic evaluations, and one customer does not require service priority. These findings underscore the importance of a nuanced approach to customer management and strategic decision-making to enhance overall profitability. By implementing TDABC, companies can more accurately allocate costs and identify key areas for improvement in customer service and profitability.